Pengaruh Work Life Balance Dan Beban Kerja Terhadap Kinerja Karyawan Dengan Stres Kerja Sebagai Variabel Intervening Pada RSJ Prof. HB. Saanin Padang - Sinta Lestari (CV. ITTC INDONESIA, 2026)
This study aims to analyze the effect of Work Life Balance and Workload on Employee Performance with Work Stress as an intervening variable at Prof. Dr. HB. Saanin Mental Hospital Padang. This research used a quantitative approach with a survey method through questionnaires distributed to 80 employees of the hospital. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results show that: (1) Work Life Balance has a positive and significant effect on Work Stress, (2) Workload has a positive and significant effect on Work Stress, (3) Work Life Balance has a positive and significant effect on Employee Performance, (4) Workload has a positive and significant effect on Employee Performance, (5) Work Stress has a positive and significant effect on Employee Performance, (6) Work Life Balance has a positive and significant effect on Employee Performance through Work Stress as an intervening variable, and (7) Workload has a positive and significant effect on Employee Performance through Work Stress as an intervening variable. These findings indicate that managing work-life balance and workload distribution properly is essential in improving employee performance through effective stress management. This study provides practical implications for hospital management in developing human resource policies that prioritize employee well-being and organizational performance.